Model Kerjasama Build-Operate-Transfer (BOT) Dalam Pengelolaan Pasar Turi Baru di Surabaya - Rafani, Syafela Ristia; Azmi, Muh. Ulul; Musleh, Moh.; Tamrin, M. Husni (Department of Public Administration, Muhammadiyah University of Makassar, 2024)
Pasar Turi Baru in Surabaya was built and managed using the Build-Operate-Transfer (BOT) cooperation model, where the private sector, namely PT. Gala Bumi Perkasa builds and manages it within a certain period of time and after that it will be returned to the Surabaya City Government as a regional asset. The construction of the new Turi market was due to a fire at the old Turi market several years ago. With the existence of Pasar Turi Baru, it is hoped that it will return to its glory days and carry a more modern concept. Even though it has only been operating for a year, the management of this new turi market has encountered an obstacle, namely competition with online markets which has made this new turi market quite empty of traders and visitors. This research uses a qualitative descriptive approach by collecting data using interviews, observation and documentation. The theory used in this research is Leonhardt's partnership theory, where there are 4 principles of success in carrying out public private partnerships, namely 1). Transparency and commitment, 2). Supervision in partnerships, 3). Negotiation process, and 4). Equality of roles in partnerships. The results of this research show that this partnership is running quite well where this collaboration is quite transparent and the existing commitment is also based on the existence of a cooperation contract and the monitoring system is running optimally, the negotiation process is also running smoothly because there is still minimal conflict, and each stakeholder's role is all equivalent.